PENGARUH BOOKLET SEPSIS NEONATORUM TERHADAP PENGETAHUAN DAN KEMAMPUAN IBU DALAM MENCEGAH KEJADIAN SEPSIS NEONATORUM - Nurhayati Nurhayati; Ria Oktavia (Maternal Child Health Care, 2021)
Neonatal sepsis is an infection that can cause severe clinical symptoms. According to the data from Kemantan Community Health Center in 2020, there were 2 cases of babies dying from neonatal sepsis and in 2021 there were 5 babies diagnosed with sepsis. The purpose of this study was determine The Effect of Neonatal Sepsis Booklet on Mother's Knowledge and Ability to Prevent Neonatal Sepsis at Kemantan Community Health Center in 2021.The type of this study was a Quasi Experiment with a one group pre-posttest design. It was conducted on January 2021 at Kemantan Community Health Center in 2021. The population was pregnant women with gestational age >36 weeks. Therewere 30 people that chosen as the samples. The data was analyzedby the Shapiro Wilk normality test and the T-Test with 95% confidence degree.The results showed that the average value of mother's knowledge before being given a booklet was 57.56, SD + 11,545. After being given a booklet, they were 68.44 and SD + 8.916. While the average value of the mother's ability to prevent neonatal sepsis before being given a booklet was 5.76 and SD + 1.184. After being given a booklet, namely 7.63 and SD + 1.752. The results of the statistical test showed that there was an effect of giving booklets on increasing maternal knowledge and mother's ability to prevent the incidence of neonatal sepsis at Kemantan Community Health Center in 2021 with a p value of 0.000 <α (0.05). It is expected that midwives will be able to provide counseling using various and easy-to-understand media to increase mothers' interest in knowing health information.Keywords         : Booklet, Neonatal Sepsis, KnowledgeReferences       : 49 (2009 – 2021)